Neotectonic deformation features in plio-pleistocene coastal aeolianites: palaeoseismology and earthquake hazard implications for the Southern Cape, South Africa - Hodge, Matthew Sotheron (Department of Geological Sciences, 2014)
Deformation features within Plio-Pleistocene Bredasdorp Group coastal aeolianites within the Southern Cape, South Africa, have been studied to resolve the neotectonic history of the region, estimate the recent to current upper-crustal stress field, and infer seismic hazard. Previous studies indicate possible Quaternary faulting within the Southern Cape, major faults within the underlying geology, and a horizontal maximum compressive stress (SHmax) orientated WNWESE to NW-SE. This study utilised geological mapping, small-scale fieldwork, and remote sensing to investigate joints, faults, kink folds, cataclasites, and soft-sediment deformation features within the aeolianites. The majority of these deformation features are found proximal to the inferred traces of the Blomerus and Struisbaai faults. In places along the Blomerus Fault, the aeolianite cross-beds dip at angles of 40°-90 °, as opposed to dips of <37 ° (the angle of repose for unconsolidated aeolian sands) observed in the rest of the study area.